2016
DOI: 10.1515/aut-2016-0025
|View full text |Cite
|
Sign up to set email alerts
|

Research on Poppers Used as Electrical Connectors in High Speed Textile Transmission Lines

Abstract: This paper presents results of research on poppers used as electrical connectors connecting fragments of textile signal lines. These lines can be used in intelligent clothing for connecting electronic modules implemented in it. Intelligent (smart) clothing can be used, among others, in the health monitoring of the elderly, newborn babies, or people working in hazardous conditions, for example, firefighters and soldiers. The aim of the present study was to examine the usefulness of poppers, widely used in cloth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…One study reported preliminary positive results on the use of snap fasteners as connectors for low and medium bandwidth signal transmission along conductive textile transmission lines. 69 And standards do exist for snap fasteners, but only on their mechanical resistance when used a garment fastener. 70 Standards and further research are required to assess, for example, the number of mating cycles they can survive as an electronic connector.…”
Section: Snap Fastenersmentioning
confidence: 99%
“…One study reported preliminary positive results on the use of snap fasteners as connectors for low and medium bandwidth signal transmission along conductive textile transmission lines. 69 And standards do exist for snap fasteners, but only on their mechanical resistance when used a garment fastener. 70 Standards and further research are required to assess, for example, the number of mating cycles they can survive as an electronic connector.…”
Section: Snap Fastenersmentioning
confidence: 99%
“…Electrical connections made with mechanical gripping can incorporate rigid connectors such as poppers (snaps) used in garments to connect two different fabrics together. Lesnikowski et al are among the many researchers characterizing the quality of a popper connection [180] .…”
Section: Mechanical Grippingmentioning
confidence: 99%
“…Connections made with mechanical gripping are also used to make rigid connectors like poppers, snap fasteners, and conductive Velcro, that can be used to connect two different fabrics together [168,180,182] . These methods could be used to make the connection with a rigid connector.…”
Section: Mechanical Grippingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the transmission lines should not be distorted in the electric pulse transmitted through the transmission lines, and should minimize the signal loss. Usually, the electrical properties of the transmission lines are evaluated based on the resistance [5] and signal transmission performance such as S-parameter [6]. S-parameters can investigate the power efficiency and bandwidth in the frequency domain.…”
Section: Introductionmentioning
confidence: 99%